Relationship Analysis of Seven Harmful Ingredients Emission in Microwave Loose Cigarette Process Parameters and Cigarette Mainstream Smoke - Xue, Fang; Li, Dongliang; Dai, Ya; Zhen, Jian; He, Rong; Zhou, Xuezheng; Wang, Peng; Li, Feiyu; Song, Guangfu (Asian Journal of Chemistry, 2011)
In this study, experiments and design were conducted with the method of uniform design about microwave loose cigarette process parameters. Emission of seven harmful ingredients i.e., carbon monoxide, hydrogen cyanide, 4-(methylnitrosamino yl)-1-(3-pyridyl)-1-butanone (NNK), ammonia, benzo[a]pyrene (BaP), phenol and crotonaldehyde in each sample were detected. With regression analysis, genetic algorithms and other data processing methods, the data in results was processed and optimized. The results highlight the following aspects of findings: (1) Adjusting the process parameters of microwave loose and the greatest relative amplitude of emission of carbon monoxide, hydrogen cyanide, 4-(methylnitrosamino yl)-1-(3-pyridyl)-1- butanone, ammonia, benzo[a]pyrene, phenol and crotonaldehyde in the smoke of samples reached 6.64, 15.6, 15.45, 11.69, 14.06, 39.62 and 31.29 % respectively. (2) Establishing a polynomial regression equation of emission and process parameters of seven harmful components in microwave loose proves, which further enabled the realization of the integration of process parameters of low crotonaldehyde emission through the optimization of process parameters of the minimum goal, while determined significant factors of the microwave loose process affecting seven harmful ingredients.